Mewujudkan Generasi Muda yang Berdaya Saing untuk Masa Depan Bangsa - Mochamad Reza Alawi; Sindi Putri Aryani; Reza Mauldy Raharja (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
The purpose of this research is to make the younger generation aware of the importance of increasing their potential to compete in the world of work because given the current global situation which is increasingly competitive. The research method used is a qualitative research method using data collection techniques carried out by triangulation (combined). The results of this study are that the younger generation is said to be competitive if it has the ability to adapt to change, solve problems, think creatively, and communicate well. With the level of education in Indonesia, the quality still needs to be improved. Skills and competencies must continue to develop in the midst of the progress of the current global era. The innovation and creativity of the younger generation has developed positively, this must continue to be monitored for the nation. Character development is also important because it can create independent, resilient and confident young people who are ready to compete in the world of work. The readiness of the younger generation in the world of work also needs to be considered with higher and tiered levels of education being one of the efforts to improve quality in competing in the world of work.